EVIDENCE ON HOT SPOT IN CONTACT BINARY VW CEPHEI - Pustylnik, I. B.; Niarchos, P. G. (Одеські астрономічні публікації, 2017)
We study the nature of asymmetry and the intrinsic variability in the light curves of VW Cep. We analyze our own B,V light curves as well as the other data from literary sources. In view of the presence of significant intrinsic brightness variations at a level of 0m.01 - 0m.03 on time scales comparable to the orbital period we deal only with individual light curves sampled possibly in one-two consecutive orbital cycles. The evidence for the presence of the small hot spot region close to the neck connecting both components will be summarized: a) displacements of the brightness maxima from the predicted epochs of elongations suggestive of an additional energy input supposedly of the hot chromospheric origin, b) the overall pattern of asymmetry in brightness maxima and minima, c) systematic colour changes with the orbital phase, d) the presence of significant cosine odd harmonics in truncated series of the observed light curves. We find that the hot spot with a characteristic size of R ∼ 0.7 - 1.2 Х 1010cm and the temperature contrast ΔT/T = 1.3 - 1.4 located on the surface of a more massive star can explain the afore-mentioned peculiarities whereas model light curves based on our model give rather good fit to the observed data studied so far. The possible physical nature of the hot spot in the light of our results confronted with the spectroscopic data (specifically Mg II resonance doublet) and flare activity signatures are briefly discussed.